Pain response and quality of life assessment in patients with moderate/severe neuropathic pain due to bone metastasis undergoing treatment with palliative radiotherapy and tapentadol: A prospective multicentre pilot study. Issue 6 (29th July 2020) - Cacicedo, Jon; Ciria, Juan Pablo; Morillo, Virginia; Martinez‐Indart, Lorea; Gómez‐Iturriaga, Alfonso; del Hoyo, Olga; Büchser, David; Frias, Andere; San Miguel, Iñigo; Suarez, Fernan; Casquero, Francisco
Abstract: Introduction: To assess pain response rate (RR) and quality of life (QoL), in patients with moderate/severe neuropathic pain (NP) due to bone metastasis (BM) undergoing palliative 3D radiotherapy plus tapentadol. Methods: We conducted a prospective multicentre pilot study. Patients were assessed before radiotherapy using the validated questionnaire (Douleur Neuropathique en 4 questions). Response to radiotherapy (8 Gy–30 Gy/1–10fr) at one and two months was assessed according the International Bone Metastases Consensus criteria. Inclusion criteria: radiological evidence of BM, NP according to DN4 (cut‐off score ≥ 4), no spinal cord compression, worst pain score ≥ 5/10. Nonparametric Mann–Whitney U test compared changes in QoL among response groups. Results: Seventeen patients (13 men, 4 woman), median age 67 years (42–81), were included. Pre‐treatment median pain severity was 7.5 (5–10). Median dose of tapentadol administered before radiotherapy was 100 mg/24 h (100–300 mg). Overall RR 1 month after radiotherapy was 10/16 = 62.5%: 3/16 (18.8%) achieving a complete response (CR) and 7/16 (43.8%) a partial response (PR). Overall RR 2 months after RT was 5/10 (50%): 10% a CR and 40% a PR. ITT RR for this study at 1 and 2 months was 10/17 = 59% and 5/17 = 29%, respectively. Patients responding to radiotherapy had significant improvement in EORTC QLQ‐C30 emotional functioning (EF) (p = 0.025) and fatigue symptom scale scores (p = 0.035) one month after radiotherapy. Painful site symptom QLQ‐BM22 scores improved 2 months after radiotherapy (p = 0.024). Conclusions: Palliative radiotherapy plus tapentadol shows an acceptable pain response and QoL improvement especially regarding EF, fatigue and painful site symptom scales in patients with moderate/severe NP due to BM. Therefore, it could be an alternative to manage NP in daily practice.